The relationship between receptive and productive vocabulary knowledge: a perspective from vocabulary use in sentence writing. Issue 4 (8th August 2018) - Zhong, Hua Flora
ABSTRACT: The progression from receptive vocabulary knowledge to productive word use in language learning to date is unclear. Vocabulary size has been the primary focus of receptive and productive vocabulary research. The present study looks at the internal structure of vocabulary knowledge along the receptive and productive continuum within a multi-aspect framework informed by Nation [2001. Learning Vocabulary in Another Language. Cambridge: Cambridge University Press] and Coxhead [2007. Factors and aspects of knowledge affecting second language word use in writing. In Teaching and Learning Vocabulary in Another Language, ed. P. Davidson, C. Coombe, D. Lloyd and D. Palfreyman, 331–42. Dubai, UAE: TESOL Arabia]. It explores the relationship between receptive knowledge of meaning, form, word class, collocation and association and productive vocabulary knowledge, in particular the controlled productive word use in sentence writing, with a multi-task approach. Participants are 620 Year 8 English as a foreign language learners from two secondary schools in China. Results provide empirical evidence to the multi-aspect construct of receptive and productive vocabulary knowledge. The study describes the contribution of each aspect to controlled productive word use in context, and offer insights into the use of existing vocabulary assessment instruments to attain this goal. The findings have important pedagogical implications for vocabulary teaching and learning, as well as for instruments selection for vocabulary knowledge assessment and research purpose.